Evaluation of the Antioxidant and Anti-Lipoxygenase Activity of Berberis vulgaris L. Leaves, Fruits, and Stem and Their LC MS/MS Polyphenolic Profile - Anna Och; Marta Olech; Kamil Bąk; Sebastian Kanak; Anna Cwener; Marek Cieśla; Renata Nowak (MDPI AG, 2023)
Berberis vulgaris L. is currently widely studied for its antioxidant and chemopreventive properties, especially with regard to the beneficial properties of its fruits. Although the bark and roots have been well known and used in traditional medicine since ancient times, little is known about the other parts of this plant. The aim of the research was to determine the antioxidant and LOX inhibitory activity effects of extracts obtained from the leaves, fruits, and stems. Another aim of the work was to carry out the quantitative and qualitative analysis of phenolic acids, flavonoid aglycones, and flavonoid glycosides. The extracts were obtained with the use of ASE (accelerated solvent extraction). The total content of polyphenols was determined and was found to vary depending on the organ, with the highest amount of polyphenols found in the leaf extracts. The free radical scavenging activity of the extracts was determined spectrophotometrically in relation to the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical, with results ranging from 63.9 mgTE/g for the leaves to 65.2 mgTE/g for the stem. Antioxidant activity was also assessed using the ABTS test. The lowest value was recorded for the barberry fruit (117.9 mg TE/g), and the highest level was found for the barberry leaves (140.5 mgTE/g). The oxygen radical absorbance capacity test (ORAC) showed the lowest value for the stem (167.7 mgTE/g) and the highest level for the leaves (267.8 mgTE/g). The range of the percentage inhibition of LOX was determined as well. The percentage inhibition of the enzyme was positively correlated with the sum of the flavonoids, TPC, TFC, and the content of selected flavonoids. Phenolic acids, flavonoid aglycones, and flavonoid glycosides were determined qualitatively and quantitatively in individual parts of Berberis vulgaris L. The content of phenolic acids, flavonoid aglycones, and flavonoid glycosides was determined with the LC-MS/MS method. The following phenolic acids were quantitatively and qualitatively identified in individual parts of Berberis vulgaris L.: gallic acid, 3-caffeoylquinic acid, protocatechuic acid, 5-caffeoylquinic acid, 4-caffeoylquinic acid, and caffeic acid. The flavonoid glycosides determined were: eleutheroside E, Eriodictyol-7-glucopyranoside, rutin, hyperoside, isoquercitin, luteoloside, narcissoside, naringenin-7-glucoside, isorhamnetin-3-glucoside, afzeline, and quercitrin. Flavonoid aglycones such as catechin, luteolin, quercetin, and eriodictyol were also determined qualitatively and quantitatively.